Respuesta :
First you want to multiply everything in the parenthesis by 4.
4 * 8y^2 = 32y^2
4 * -9 = -36
Then add your like terms
4y^2 + 32y^2 - 36
36y^2 - 36
Hope this helps!
4 * 8y^2 = 32y^2
4 * -9 = -36
Then add your like terms
4y^2 + 32y^2 - 36
36y^2 - 36
Hope this helps!
assuming 4y^2
4y^2 + 4(8y^2 - 9) (dont forget to distrribute)
4y^2 + 32y^2 - 36
36y^2 - 36
hope this helps , give brainliest
4y^2 + 4(8y^2 - 9) (dont forget to distrribute)
4y^2 + 32y^2 - 36
36y^2 - 36
hope this helps , give brainliest